Filipino Nursing Students’ Health Promoting Behaviors during Pandemic - Ma. Prestige Leudouel J. Diana; Pearl Zerrha Chiu; April Rhose De Silva; Ryan Michael F. Oducado; Francesca G Cercado; Pamela Andrea De Justo (Department of Nursing, Faculty of Medicine, Diponegoro University, 2023)
Background: Research on health promoting behaviors can assist nursing students in identifying, maintaining, and improving health behaviors. The notable impact and changes in lifestyle behaviors during the pandemic necessitate a closer look into students’ health-promoting behaviors. However, there is a lacuna in the literature about health promoting activities of nursing students stuck at home and attending online learning during the pandemic.Purpose: This study assessed the level and predictors of health promoting behaviors of nursing students in a Philippine public university during a pandemic.Methods: This study used a cross-sectional design with 363 out of 531 undergraduate nursing students of a public university in the Philippines as study participants. Data were gathered using an online survey last March 2022 employing the Health Promoting Lifestyle Profile (HPLP) II. Significant predictors were identified using multiple linear regression analysis with the aid of SPSS version 26.0.Results: Results showed that nursing students had a high (M=2.80 out of 5) practice of health promoting behaviors. Physical activity ranked the lowest among the six dimensions of health promotion behaviors. The variables that predicted the health promoting behaviors of nursing students were self-reported academic performance (β=2.110, p=.000), family income level (β=.055, p=.001), and academic year level (β=.057, p=.002).Conclusion: Nursing students should continue to maintain their good practice of health promoting behaviors. However, more attention should be given to engaging in physical activity to maintain holistic well-being.